(untitled) (Italian Journal of Public Health, 2005)
A new real-time PCR assay, using melting curve analysis, was developed for the rapid and reliable detection and sub-typing of influenza A and B. In order to evaluate it’s specificity, cell culture surnatants positive for Respiratory Syncytial Virus, Parainfluenza Viruses 1, 2 and 3, Measles Virus, Influenza A (to evaluate Influenza B primer) and B (to evaluate Influenza A primer) were tested and all of the results were negative. A series of Influenza A and B cell culture-grown viruses were diluted in virus transport medium, titrated and tested to determine the analytical sensibility which equated to 0.64, 0.026, 0.64, 0.62 PFU for A/H1N1, A/H3N2, Victoria-like and Yamagata-like B viruses, respectively. Twenty-five specimens, collected during the 2001/02 and 2002/03 seasons, which were positive for A/H1N1 (n = 7), A/H3N2 (n = 10), B Victoria-lineage (n = 5) and B Yamagata-lineage (n = 3), were tested in order to evaluate the assay’s clinical sensitivity, all of the results were positive. The new real-time PCR appears to be a suitable tool for virological surveillance and the diagnosis of respiratory infections